Design Thinking-Based STEM Learning: Preliminary Results on Achieving Scale and Sustainability Through the IGNITE Model - Dotson, Mary Elizabeth; Alvarez, Valentina; Tackett, Maria; Asturias, Gabriela; Leon, Isabela; Ramanujam, Nirmala (Frontiers in Education, 2020)
Solutions to the most pressing global issues require creative innovators, critical thinkers, and problem-solvers. Yet rural communities globally often lack the resources to provide adequate STEM design-thinking coursework at the primary and secondary school level. Ignite is a novel approach to STEM curricula, providing a framework that addresses this disparity by using design thinking. Students are empowered to understand the sustainable development goals (SDGs) through the development of technological solutions to community or health problems; problems they may relate to or directly experience. Each Ignite curriculum follows a basic formula: (1) students learn a specific set of engineering skills, (2) students work in teams to use the human-centered design process, and (3) they develop a solution to a (SDG) using the engineering skills they learned. Ignite began with just 4 undergraduate students who participated in a design-thinking biomedical engineering course taught at Duke University. Through evidence-based peer-led co-learning model, 79 additional students from Guatemala and the U.S. have become trainers and have taught more than 1,500 students across 16 school in Guatemala since 2017 with preliminary data suggesting the program has a positive impact on student perceptions of STEM the inaugural school where Ignite was launched Instituto Indigena Nuestra\ Senora del Socorro (IINSS). Preliminary data suggests that this program is both scalable and sustainable due to its peer-led, student learning model and due to a local partner, FUNDEGUA, who is managing the implementation of Ignite locally in Guatemala.